Ethiopian EFL Students’ Willingness to Communicate (WTC) and the Factors Associated With It in Oral Communicative English Classes - Teshome Abebe, Dereje; Syoum Weldemariam, Getachew; Legese Birassa, Guta (GIST – Education and Learning Research Journal, 2024)
Communication, particularly verbal communication, is central to the development of a desired competence in a second or foreign language. Approaches such as communicative language teaching (CLT) in second language acquisition emphasize practical use of the target language for effective learning/acquisition. However, despite the necessity of using a target language to learn it, it has been a common phenomenon to observe most learners exhibiting passiveness, reticence, and unwillingness to participate in oral communicative opportunities in English as a foreign language (EFL) classes. This study therefore explored EFL students’ willingness to communicate (WTC) in oral communicative English classes together with the factors underlying with it in the Ethiopian higher education context. To this end, primary quantitative data were collected from a randomly selected sample of 450 EFL students taking oral communicative English courses followed by qualitative data from a sample of fifteen students selected again randomly to triangulate the results from the quantitative data. The results revealed that the target students had in general a low level of WTC in oral communicative English classes, and their WTC was affected by both psychological and contextual factors such as self-confidence, motivation, personality, language learning orientation and classroom environments. The findings indicate that EFL students’ WTC is a crucial component to increase students’ participation in oral communicative English classes by raising their self-confidence, motivation and awareness of language learning orientations, coupled with facilitating the language learning environment. It is therefore suggested that WTC needs to be given special consideration while designing and preparing ELT materials, and during instructions as well.